Single application of a new polymer-coated urea improves yield while mitigates environmental issues associated with winter wheat grown in rice paddy soil - Shen, Yazhen; Wang, Baichun; Zhu, Sixi; Xie, Wei; Wang, Shenqiang; Zhao, Xu (Field crops research, 2022)
Rainfed winter wheat grown in rice paddy suffers from a relatively low yield and severe nitrogen (N) losses. Reduction in N application and/or single use of controlled release N fertilizer (CRNF) have been proposed to address these challenges. A new CRNF, known as nano-FeIII-tannic acid-modified waterborne polymer-coated urea (NWU), has the ability to avoid initial quick release and prolong N availability, which is assumed to synchronize with winter wheat N uptake. Here, we conducted a field experiment spanning three wheat growing seasons to examine the efficacy of single application of NWU on grain yield, N uptake, N use efficiency (NUE), reactive nitrogen (Nr) losses, and net ecosystem economic benefit (NEEB) under two N application rates (160 and 240 kg ha−1). Basal application of NWU increased grain yield by 15.7 %, NUE by 51.1 % and NEEB by 45.1 %, while reducing Nr losses by 35.7 % compared to three-split applications of urea at 240 kg ha−1. Moreover, single application of NWU with a reduced N rate by one-third could even maintain high grain yield and NEEB comparable to that of conventional N practices, meanwhile reducing Nr losses by 58.8 %. Single application of NWU can address high yield and environmental protection simultaneously for wheat grown in paddy soil. [Display omitted] •The priority is to use CRNF for wheat grown in paddy fields.•Nano- FeIII-tannic acid modified displayed more synchronized nitrogen supply.•Single use of the modified CRNF achieved largest yield and economic benefit.•Single use of the modified CRNF coupled with N reduction minimized Nr loss.